(UI) USER INTERFACE DESAIN PADA WEB MOVE SABLON SRAGEN SEBAGAI MEDIA PROMOSI - Christian Dwita Nugraha; Evelyne Henny Lukitasari; Yudi Wibowo (Canthing, 2024)
Move Screen Printing is a screen printing business established in the city of Sragen which was founded by Arief Mutaqin on December 3 2020, precisely in Bedoro village, Sragen, Central Java. Several entrepreneurs, one of whom is Move Screen Printing, are having difficulty marketing their products. apart from the impact following the COVID 19 pandemic, locations in remote areas are a problem. The solution offered is marketing through a supporting website. A supportive website is a website that makes it easy for users to access it, supported by a good user interface (UI). further developed with creative ideas, design and evaluation in the design process. It is hoped that the user interface (UI) design of this website will become Move Sablon's personal identity and make it easier to purchase and market Move Sablon products. Keywords: Design, UI User Interface, Website, Promotional Media